Association of pharmacotherapy with clinicians' nutritional counseling practices to diabetic and hypertensive patients - Deldar Morad Abdulah; Saeid Kider Ahmed; Raghib Mustafa; Mahir Sadullah Saeed (Wolters Kluwer Medknow Publications, 2021)
Background: Nutrition counseling is an important tool for encouraging healthy nutrition behaviors among individuals. The nutritional imbalance is rising worldwide, leading to the emergence of various diseases. Physicians have an important role in impeding healthy nutrition in patients. Aims and Objectives: The role of patients prone to pharmacotherapy on nutritional counseling and management (NCM) practices of clinicians to patients with diabetes or hypertension in the routine clinical practice was explored in this study. Materials and Methods: In this cross-sectional study, a total of 267 clinicians, including family doctors, general practitioners, and internists were purposively included. The attitudes toward NCM and their practices in routine clinical working were examined through the self-reported technique. Results: The mean age of the physicians was 34.18 and had experience for 5 years. A small percentage of them have completed the nutrition training course (26.59%). The study showed that different kinds of NCM, including nutritional assessment, therapy, and education, were presented to diabetic and hypertensive patients. The majority of the physicians emphasized their role (88.1%) in promoting nutritional therapy. Besides, most of them (88.0%) mentioned that a high priority must be given to NCM in routine clinical practice. The prone of patients to pharmacotherapy rather than diet therapy was determined to be a barrier to the NCM to diabetic and hypertensive patients. Conclusions: This study showed that physicians had good attitudes toward NCM; however, the prone of the diabetic and hypertensive patients to pharmacotherapy rather than diet therapy impedes the NCM by clinicians.